Disease burden and functional outcomes in congenital myotonic dystrophy: A cross-sectional study. (12th July 2016) - Johnson, Nicholas E.; Butterfield, Russell; Berggren, Kiera; Hung, Man; Chen, Wei; DiBella, Deanna; Dixon, Melissa; Hayes, Heather; Pucillo, Evan; Bounsanga, Jerry; Heatwole, Chad; Campbell, Craig
Abstract : Objective: Herein, we describe the disease burden and age-related changes of congenital-onset myotonic dystrophy (CDM) in childhood. Methods: Children with CDM and age-matched controls aged 0 to 13 years were enrolled. Participants were divided into cohorts based on the following age groups: 0–2, 3–6, and 7–13 years. Each cohort received age-appropriate evaluations including functional testing, oral facial strength testing, neuropsychological testing, quality-of-life measurements, and ECG. Independent-samples t test or Wilcoxon 2-sample test was used to compare the differences between children with CDM and controls. Probability values less than 0.05 are reported as significant. Results: Forty-one participants with CDM and 29 healthy controls were enrolled. The 6-minute walk was significantly different between CDM (258.3 m [SD 176.0]) and control participants (568.2 m [SD 73.2]). The mean lip force strength was significantly different in CDM (2.1 N [SD 2.8)] compared to control participants (17.8 N [SD 7.6]). In participants with CDM, the mean IQ (65.8; SD 18.4) was 3 SDs below the mean compared to standardized norms. Measurements of grip strength, sleep quality, and quality of life were also significantly different. Strength measures (oral facial strength, grip strength, and 6-minute walk) correlated with each other but not with participant IQ. Conclusions: This work identifies important phenotypes associated with CDM during childhood. Several measures of strength and function were significantly different between participants with CDM and controls and may be useful during future therapeutic trials.